Entrepreneurial financing: Program review and policy perspective - Ham, Jin Joo (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Entrepreneurial financing3, such as publicly initiated venture capital or grant schemes, serves as an important policy instrument that aims to bridge the financing gap facingyoung, innovative businesses, a gap that is mainly due to higher risk and growing uncertainty, and to strategically promote the creation of new ventures through the revitalization of their venture capital industries. This study examines public venture capital initiatives in Australia, Canada, and Sweden, and discovered that all three countries actively foster their venture capital industry through the formation of funds or the provision of tax incentives. It is notable that the majority of financing initiatives heavily depend on supply-side measures rather than demand-driven policies that focus on stimulating private investment in technological innovations and discoveries. This paper discusses in-depth the policy impact of public financing initiatives and their subsequent side-effects raised in the process such as overlapping in funding structure across the country, lack of monitoring and evaluation for feedback, fragmentation across the government ministries and agencies, and competition with the private sector, which may cause inefficiency as a result of public intervention. Financial constraints may arise for many reasons, partly resulting from the lack of investment readiness of young entrepreneurs. This signals a policy shift towards the creation of market-driven demand away from the traditional supply-push approach, and is a grand challenge to policymakers in entrepreneurial financing. Attention is leaning towards the efficiency and effectiveness of these public-financing initiatives in terms of their policy roles. It is worth noting that policy should focus on generating synergy so available resources can be channeled into the early, risky stage of new ventures, working as a facilitator to the achievement of an intended policy goal.